SEXUAL VIOLENCE ON WOMEN IN INTERNATIONAL AND HUMANITARIAN LAW PERSPECTIVE - Aini Turmaningsih; Gearysta Yoransyah; Natasha Dwi Septiawani; Widy Amalia Haris; Nazaruddin Lathif; Sapto Handoyo Dp (Scholar Express Journals, 2022)
Violence against women is a problem of violations of humanitarian law and also an international law that often occurs, one of which is in armed conflict. The purpose of this research is that these problems can be solved in it. Victims of violence against women reached 80% including adults and children, which exceeded the number of victims in the military. The consequences created by sexual violence in armed conflict are very serious, one of which is mental disturbance. To analyze the impact of violence on women with the traditional view that considers women as property. The method used in this study is a type of normative legal approach by examining the applicable laws and regulations. In general, this research is expected to be able to describe and explain to readers regarding sexual violence that often occurs in armed conflicts and outside the region based on a juridical study of international law and court practices.
Keywords: Sexual violence; women; armed conflict